Analisis Risiko Likuiditas dan Risiko Solvabilitas untuk Mengetahui Kondisi Keuangan pada Perumda Bank Perkreditan Rakyat (BPR) Purwakarta yang Terdaftar di OJK Tahun 2018-2022 - Tita Sri Rahayu; Rola Manjaleni (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
People's Credit Banks (BPR) are financial institutions that play a crucial role in collecting and channeling funds. This research focuses on evaluating the financial condition of Perumda People's Credit Bank (BPR) Purwakarta from 2018 to 2022. The aim is to analyze or assess the financial situation during this period using ratios that measure liquidity risk and solvency risk. The research method used is quantitative descriptive by calculating ratios related to liquidity risk (liquidity risk ratio, deposit risk ratio) and solvency risk (risk assets ratio, secondary risk ratio). The data used in this research is secondary data obtained from publications by the Financial Services Authority (OJK). Based on the calculation results, it is found that Perumda BPR Purwakarta, in terms of liquidity risk, has had a good financial condition during the period of 2018-2022. However, it faces financial issues regarding solvency, as indicated by the financial reports for the years 2018, 2019, 2020, and 2022, leading to financial risks in meeting its long-term obligations.